Analisis Video Cerita Pendek "The Paper Menagerie" Oleh Ken Liu Sebagai Media di Pembelajaran Karya Sastra - Nabila Fasicha Mardlotillah; Meria Zakiyah Alfisuma; Tri Pujiati (EL2J (English Language and Literature Journal), 2023)
A literary work is an imaginative idea written by an author. To introduce literary works, interesting learning media are needed. Thus, learning innovation needs to be practiced. One of the innovations in teaching literary works can be practiced with the use of ICT, for example, learning video. Character analysis videos of ‘The Paper Menagerie’ by Ken Liu can be used as a literary learning medium. This descriptive qualitative study uses the theory of literary learning media by Kem and Dayton to analyze the use of short story analysis video as a media in teaching and also to analyze the main function of that media. Then the theory of character by Egri Lajos will be applied to analyze the three dimensions of character that has been explained in the video. The research shows that the video analyzing the Short Story “The Paper Menagerie” By Ken Liu fulfills the three main functions of literary learning media. They are first, the discursive methods of motivation of interest or action, second, the media present information, and third the media giving incursion. In conclusion, the character analysis video of the short story “The Paper Menagerie” by Ken Liu could be used as a learning medium.